CAPACITY EXPANSION AND INSTALLATION OF SURGE PROTECTION DEVICE IN SOLAR POWER PLANT SYSTEM FOR HYDROPONICS FARMER - Rizki Putra Prastio; Prisma Megantoro; Jati Galih Satrio; Ihsan Nurkhotib; Nara Atthama; Irfan Helmi Sukmawan; Rizky N. Rachman; Ismayahya Ridhan Mutiarso (Jurnal Layanan Masyarakat, 2023)
Community service has been carried out in Pasuruan, Eastern Java. A hydroponics farming system, run by a group of farmers in Kecamatan Gempol, consumes electric energy provided by a 900 Wp solar power system. The power plant is equipped with two batteries, 12 V 100 Ah, with a Depth of Discharge (DoD) of 80% each, which enables the power system to store the energy of 1920 Wh as a reserve. According to the farmer’s report, one of the essential components in the solar power system was damaged twice due to lightning strikes at an adjacent time. Also, the hydroponics system is unable to run all night continuously due to the insufficient capacity of the storage system. Therefore, surge protection devices (SPD) are installed in the solar power plant system to protect crucial components from damage caused by lightning strikes. Furthermore, this activity adds two more batteries to the system that double the energy reserve to extend the operating hours of hydroponics electrical equipment when sunlight is unavailable. The work also created a new hydroponics platform with 126 holes as a part of capacity expansion to meet the market demands. Extra protection against insects is also provided by shielding the hydroponics platforms close to the bushes with the insect net.